2015
DOI: 10.3109/15563650.2015.1113543
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in pediatric medication exposure: Spatial analysis of poison center utilization in western Pennsylvania

Abstract: Context Medication drug exposures among young children continue to rise despite current poison prevention efforts. These exposures result in increased healthcare utilization and medical costs. New tactics are needed to reduce injuries related to pediatric drug exposures. Objective We aimed to identify cluster patterns in 1) calls for pediatric medication drug exposures and 2) a subset of calls that resulted in medical evaluation referrals. We identified and evaluated population characteristics associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…These results are inconsistent with numerous studies that have shown that TE in children occurred more frequently in lower socioeconomic groups. 5,6,13,24 However, studies have suggested that higher socioeconomic status (SES) is associated with "party" drug abuse, such as γ-hydroxybutyrate (GHB), while injectable drugs are associated with lower SES. 17,25 Further research can be done to analyze different potential poisoning exposures and SES.…”
Section: Lotfipour Et Almentioning
confidence: 99%
“…These results are inconsistent with numerous studies that have shown that TE in children occurred more frequently in lower socioeconomic groups. 5,6,13,24 However, studies have suggested that higher socioeconomic status (SES) is associated with "party" drug abuse, such as γ-hydroxybutyrate (GHB), while injectable drugs are associated with lower SES. 17,25 Further research can be done to analyze different potential poisoning exposures and SES.…”
Section: Lotfipour Et Almentioning
confidence: 99%
“…Descreve-se, nesta pesquisa, que os medicamentos foram identifi cados como principais agentes causadores de intoxicação infantil, permanecendo em primeiro ou segundo lugar, independentemente da faixa etária; em crianças de até três anos de idade, além dos medicamentos, os produtos de uso domiciliar também aparecem como principal agente tóxico e, a partir dos quatros anos, destacaram-se as plantas tóxicas, raticidas, alimentos e produtos químicos (Tabela 1). NGUYEN et al, 2015;TAVARES et al, 2013).…”
Section: Resultsunclassified
“…24,25 GIS has provided greater understanding of child health issues ranging from gun violence, pediatric poisoning, to vaccination rates. 19,[26][27][28] One of the most impactful application of GIS in child health has been in its role in blood lead level screening. Researchers compiled surveillance data and information on the built environment to assess children's risk for lead poisoning.…”
Section: Discussionmentioning
confidence: 99%